Jellyfish Fisheries on the Miskitu Coast: Challenges for communal governance in Post-Law 445 Nicaragua. - Fahrenbruch, Matthew L. (2018)
The Miskito Coast is a historically marginalized region of Nicaragua. Since the colonial period, the Coast has been culturally and physically isolated from the dominant mestizo Pacific. For years, the ‘costeño’ population has demanded greater autonomy over local governance. The passage of Law 445 has devolved, on paper, some governance responsibilities to communal and territorial governments, however, challenges remain. I focus here on the challenges faced by communal governments when dealing with non-traditional externally generated extractive projects. I consider specifically the development of the jellyfish fishery that began in 2008. My results suggest that communal governments still play only a minor role in the development of their natural resources, lack advocacy, and are at a significant power and knowledge disadvantage when it comes to negotiations with external actors. Even after approval, communities lack systems of accounting for extracted resources and have few avenues for capturing proceeds from extraction activities.